Strategic-prospective analysis of a case: refrigerated slaughterhouse of alternative meats in the province of La Pampa (Semiárida, 2018)
Normative prospective is used in the strategic analysis of micro, meso and macro organizational systems. Based on the study of a refrigerated slaughterhouse for alternative meats in the province of La Pampa, where primary and secondary information is collected and triangulated in depth, an analysis model is proposed that starts from a desired situation, built based on the reflection of values (non-neutral analysis based on concrete-utopia). Based on this situation, the current situation is criticized and a situation for improvement is proposed (with objectives and times). With these three situations, the particular problem is limited to moving from the current situation to that of improvement in the given time considering the desired situation. The Case presented a series of dynamic and restrictive forces, mainly related to the markets for inputs and products, and to the internal articulation between management and operational personnel. The resulting strategic alternatives focus on a) stabilizing links with suppliers, b) improving the purchasing logistics process, c) organizational and administrative restructuring, and d) generating added value at source. The methodological framework made it possible to obtain and triangulate quality information for the proposal of strategic alternatives from a prospective conception.